Performance evaluation and R-value analysis for thermally insulated PCM wall with fluted sheets. (2020) - Dhaya chandhran, K.S.; Jothilakshmi, M.; Mohan, A.; Tholkapiyan, M.
Abstract: At present most of the Indians are depending on non-renewable electricity power for house needs. But Non-renewable energy exploits the nature and scarce fossil fuel source. The Air conditioners are the most power consuming devices which are used to reduce the indoor temperature and refrigerate the food. These devices generate greenhouse gases which increases day by day, it Leeds in Global warming. Also the medical experts [7] are advising not to use, expose more to Air conditioners which are not maintained properly, as it stimulates problems like illness and constant fatigue, chronic illness, asthma and skin allergy. In order to overcome such problems, an alternate solution is recommended by implementing a new method of construction and materials. This is a new attempt by implementing a system of cavity wall in a building structure with water and air in the cavity with the help of embedding the fluted sheets in the exterior walls of building (Kamal et al., 2015) [1]. The advantage of this system is reduces 17% of thermal conductivity and electricity consumption is 810 time lesser than air conditioning room, which increases the sustainability of natural sources. Finally the constant-R (Thermal resistivity) value is arrived for composite materials with water.